Parental Involvement as an Antidote to Student Dropout in Higher Education: Students’ Perceptions of Dropout Risk - Pusztai Gabriella; Hrabéczy Anett; Csók Cintia (Open Education Studies, 2025)
Since the expansion of higher education began, student motivation and institutional choice have been widely studied, yet the reasons behind high dropout rates in public institutions in Central and Eastern Europe remain poorly understood. In our research, we sought to answer the question of what subjective and objective factors predict an increased risk of dropping out. We analyzed the views of students who had already dropped out and active students in our empirical research database (N = 1,502), recorded in 2018–19. A large-scale questionnaire survey was conducted to examine students’ perceptions. We hypothesized that family background, academic motivational factors, and external and internal institutional networks each have an independent impact on the perception of dropout risk in both groups studied. Our results, based on multivariable analysis, show that the effect of individual sociodemographic factors is significant. However, parental involvement clearly proved to be the strongest protective factor, along with the positive effect of institutional intergenerational support and intrinsic motivation for further education. We recommend that institutions develop a comprehensive strategy to enhance family support and reinforce the role of extracurricular activities in higher education.